Enhanced Intergenerational Occupational Mobility through Trade Expansion: Evidence from Vietnam - Devashish Mitra; Hoang Pham; Beyza Ural Marchand (Institute of Labor Economics (IZA), 2022)
Using eight rounds of the Vietnam Household Living Standards Surveys (VHLSSs) spanning 16 years and exploiting the US-Vietnam Bilateral Trade Agreement (BTA) in 2001 as a large export shock, we investigate the impact of this shock on intergenerational occupational mobility in Vietnam employing a difference-in-differences research design. Our analysis suggests that the BTA has led to substantial upward occupational mobility, allowing both sons and daughters to have better occupations than their parents, with the effects being larger for daughter-mother pairs. The effect is larger in the long-run compared to the short-run. We find evidence that the driving force is an increase in skill demand via gender-biased expansion in export volumes. The effects are largely driven by intersectoral resource reallocation rather than within-sector upgrades. In addition, the BTA induced a higher likelihood of college education for both sons and daughters, but of vocational training only for sons. Overall, the BTA shock accounts for 36% of the overall increase in mobility for both genders. Our results control for Vietnam's own tariff reductions, which do not seem to have any statistically significant impact on mobility.
Keywords: F13; F16; F66; J62; O19; 330; international trade; export market access; intergenerational mobility